Stories of successful adaptations of immigrant students in the Polish educational system – perspective of EFL teachers - Nosidlak, Katarzyna (Neofilolog, 2023)
As a result of increasing numbers of immigrants, Poland is currently in the process of transition from a predominantly mono-lingual/cultural to multilingual/cultural country. Consequently, a constantly rising number of foreign students is joining Polish schools, who face the need to adapt to new social and institutional settings. In response to this demographic trend, the main aim of this paper is to point to the role of different factors recognised as facilitating in the process of school adaptation in the case of immigrant students in the Polish educational system. The research participants, 23 Polish teachers of English, in semi-structured interviews, described over 60 cases of multilingual children they used to work with. Out of these, the accounts describing primary school learners who had adapted well to new educational environments were selected for qualitative analysis, conducted with the aid of NVivo Software. In this case study, the stories of four successful adaptations have been selected to illustrate the importance of factors recognised in the analysis as those which favourably assist the process of school adjustment. These include: (1) the individual dispositions of the newcomer, (2) the behaviours of their classmates, (3) the supportive actions of teachers, (4) parents’ engagement and assistance.